Positive electrode active material and method for producing same

By forming a cobalt-containing coating and island portion on a lithium transition metal oxide in the form of a single particle, the problem of particle collapse of high nickel positive electrode active materials under high electrode density is solved, and high energy density and excellent life characteristics are achieved.

CN119522490APending Publication Date: 2025-02-25LG CHEM LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380037358.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-20
Filing Date
2023-05-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing high-nickel positive electrode active materials are prone to particle collapse under high electrode density, resulting in reduced energy density and deterioration in life characteristics.

Method used

A lithium transition metal oxide is used in the form of a single particle, and a cobalt-containing coated portion and an island portion are formed on its surface. The island portion contains 0.08-2.50 mole% aluminum or zirconium, and a layered structure of nickel-cobalt-manganese (NCM) oxide is formed by heat treatment.

Benefits of technology

A positive electrode active material with high electrode density has excellent life characteristics and output characteristics, reducing the NiO layer, reducing resistance, and improving energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522490A_ABST
    Figure CN119522490A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material and a method for manufacturing the same, the positive electrode active material comprising: a lithium transition metal oxide in the form of a single particle and divided into a surface portion and a core; a coating part which is formed on the surface part and contains cobalt; and an island part which is discontinuously formed on at least one selected from the group consisting of the surface part and the coated part, in which the island part contains 0.08-2.50 mol% of at least one selected from the group consisting of aluminum (Al) and zirconium (Zr) based on the total number of moles of the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the priority of Korean Patent Application No. 10-2022-0062251 filed in the Korean Intellectual Property Office on May 20, 2022, the disclosure of which is incorporated herein by reference in its entirety.

[0002] The invention relates to a positive electrode active material and a method for preparing the same. Background Art

[0003] In recent years, with the development of technology such as electric vehicles, the demand for high-capacity secondary batteries has been increasing, and accordingly, research on positive electrodes using high-Ni positive electrode active materials having excellent capacity characteristics has been actively conducted.

[0004] Since the high-Ni positive electrode active material is manufactured using a coprecipitation method, the manufactured high-Ni positive electrode active material has the form of secondary particles in which primary particles are aggregated. However, the active material in the form of secondary particles has the disadvantage that fine cracks are generated in the secondary particles during long-term charging and discharging to cause side reactions, and when the electrode density is increased to improve the energy density, the secondary particles also cause the structural collapse of the secondary particles, thereby reducing the energy density and deteriorating the life characteristics due to the reduction of the active material and the electrolyte.

[0005] In recent years, in order to solve the problem of high nickel positive electrode active materials in the form of secondary particles, single-particle nickel-based positive electrode active materials are being developed. The advantage of single-particle nickel-based positive electrode active materials is that even when the electrode density is increased for high energy density, particle collapse does not occur. However, because single-particle nickel-based positive electrode active materials require relatively high sintering temperatures to manufacture, the layered structure of R-3m cannot be properly maintained, and as lithium is separated from the crystal structure, the phase transition is to an Fm-3m locked salt structure such as NiO and the crystallinity of the positive electrode active material deteriorates, thereby increasing the ratio of NiO on the surface of the manufactured single particle, and there is a problem that as NiO increases, the resistance increases, and the energy density and output decrease. In addition, when the sintering temperature is reduced, the single-particle nickel-based positive electrode active material exists in the form of over-sintered secondary particles, and the problem is that the effect of improving life and gas generation does not reach the level expected for a single particle.

[0006] Therefore, there is still a need to develop a positive electrode active material that has a high electrode density and exhibits excellent life characteristics and output characteristics.

[0007] [Prior art literature]

[0008] [Patent Document]

[0009] (Patent Document 1) KR 2019-0094529 A1 Summary of the invention

[0010] Technical issues

[0011] One aspect of the present invention provides a positive electrode active material having a high electrode density and exhibiting excellent life characteristics and output characteristics.

[0012] Another aspect of the present invention provides a method of manufacturing a positive electrode active material having a high electrode density and exhibiting excellent life characteristics and output characteristics.

[0013] Technical Solution

[0014] In order to solve the above problems, the present invention provides a positive electrode active material.

[0015] (1) According to one aspect of the present invention, there is provided a positive electrode active material, comprising: a lithium transition metal oxide in the form of a single particle and divided into a surface portion and a core; a coating portion formed on the surface portion and containing cobalt; and an island portion discontinuously formed on at least one selected from the surface portion and the coating portion, wherein the island portion contains 0.08-2.50 mol % of at least one selected from aluminum and zirconium based on the total molar number of the positive electrode active material.

[0016] (2) In the above (1) of the present invention, there is provided a positive electrode active material wherein the island portions are dispersed and distributed on a surface of at least one selected from the surface portion and the coating portion.

[0017] (3) In the above (1) or (2) of the present invention, there is provided a positive electrode active material, wherein the island portion contains 0.13 to 2.50 mol % of aluminum based on the total molar number of the positive electrode active material.

[0018] (4) In any one of the above (1) to (3) of the present invention, there is provided a positive electrode active material, wherein the island portion contains 0.08 mol % to 2.50 mol % of zirconium based on the total moles of the positive electrode active material.

[0019] (5) In any one of the above (1) to (4) of the present invention, there is provided a positive electrode active material, wherein a total area of ​​the coating portion is 10% to 100% based on a total area of ​​an outer surface of the lithium transition metal oxide.

[0020] (6) In any one of the above (1) to (5) of the present invention, there is provided a positive electrode active material, wherein the surface portion is a region extending from the outermost surface of the lithium transition metal oxide in the form of a single particle to a depth of 1 nm to 50 nm in a direction toward the center.

[0021] (7) In any one of the above (1) to (6) of the present invention, there is provided a positive electrode active material wherein the average oxidation number of nickel contained in the surface portion is from +2.36 to +3.00.

[0022] (8) In any one of the above (1) to (7) of the present invention, there is provided a positive electrode active material wherein cobalt and nickel satisfy a Co / Ni value (mol / mol) of 0.1 to 0.8 based on the entirety of the surface portion and the coating portion.

[0023] (9) In any one of the above (1) to (8) of the present invention, there is provided a positive electrode active material wherein the coating portion is located in the form of islands on the outer surface of the surface portion.

[0024] (10) In any one of the above (1) to (9) of the present invention, there is provided a positive electrode active material, wherein the coating portion comprises a composition of LiCoO 2 .

[0025] (11) In any one of the above (1) to (10) of the present invention, there is provided a positive electrode active material wherein the island portion contains LiCoAlO 2 .

[0026] (12) In any one of the above (1) to (11) of the present invention, there is provided a positive electrode active material, wherein the lithium transition metal oxide is a lithium composite transition metal oxide containing nickel, cobalt and manganese.

[0027] (13) In any one of the above (1) to (12) of the present invention, there is provided a positive electrode active material, wherein the lithium transition metal oxide is a lithium composite transition metal oxide represented by the following formula 1:

[0028] [Formula 1]

[0029] Li a Ni x Co y M 1 z M 2 1-x-y-z O2

[0030] Among them, in the above formula 1,

[0031] M 1 is at least one selected from Mn and Al,

[0032] M2 is at least one selected from B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, S, Sr, Ta, La, and Hf,

[0033] 1.0 ≤ a ≤ 1.3, 0.6 ≤ x < 1.0, 0 ≤ y ≤ 0.4 and 0 ≤ z ≤ 0.4.

[0034] (14) In any one of the above (1) to (13) of the present invention, there is provided a positive electrode active material, wherein the lithium transition metal oxide is a lithium composite transition metal oxide represented by the following formula 2:

[0035] [Formula 2]

[0036] Li a Ni b Co c Mn d M 1 e O2

[0037] wherein, in the above formula 2,

[0038] M 1 is at least one selected from Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S,

[0039] 0.9 ≤ a ≤ 1.1, 0.8 ≤ b < 1, 0 < c < 0.2, 0 < d < 0.2, 0 ≤ e < 0.1 and b + c + d + e = 1.

[0040] To solve the above other problems, the present invention provides a method for manufacturing a positive electrode active material.

[0041] (15) According to another aspect of the present invention, there is provided a method for manufacturing a positive electrode active material, the method comprising the following steps:

[0042] 1) Mixing lithium transition metal oxide particles in the form of single particles, a cobalt source, and at least one selected from an aluminum source and a zirconium source; and

[0043] 2) Heat-treating the mixture in step 1).

[0044] (16) In the above (15) of the present invention, there is provided a method, wherein, in step 1), an additional metal source is further mixed.

[0045] (17) In the above (15) or (16) of the present invention, there is provided a method, wherein the heat treatment in step 2) is carried out at 500 °C - 800 °C.

[0046] Beneficial Effects

[0047] The positive electrode active material of the present invention is a positive electrode active material comprising a lithium transition metal oxide in the form of a single particle, wherein the positive electrode active material has a surface portion with a reduced NiO layer while comprising a coating portion containing cobalt, thereby having a high electrode density and exhibiting excellent life characteristics and output characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 TEM and TEM EDS images (Al element map and Co element map) of a thin film sample of the positive electrode active material of Example 1 are shown.

[0049] Figure 2 A TEM EDS image (Al element map and Co element map) at another position of the thin film sample of the positive electrode active material of Example 1 is shown. DETAILED DESCRIPTION

[0050] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.

[0051] It should be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to the meanings defined in commonly used dictionaries. It should be further understood that the words or terms should be interpreted as having a meaning consistent with their meanings in the context of the relevant fields and technical concepts of the present invention, on the basis that the inventors can appropriately define the meanings of the words or terms to best explain the principles of the present invention.

[0052] As used herein, the term “primary particle” refers to the smallest particle unit distinguished as a single mass when a cross section of a positive electrode active material is observed through a scanning electron microscope (SEM), and may be composed of a plurality of crystal grains.

[0053] As used herein, the term "secondary particles" refers to a secondary structure formed by aggregation of a plurality of primary particles. The average particle size of the secondary particles can be measured by a particle size analyzer.

[0054] As used herein, the term "single particle form" can be used interchangeably with the term "single particle type", and refers to a shape that is in contrast to the shape of secondary particles formed by the aggregation of hundreds of primary particles prepared by conventional methods. In addition, the term "single particle type positive electrode active material" or "lithium transition metal oxide in single particle form" used herein is a concept in contrast to the positive electrode active material in the form of secondary particles formed by the aggregation of hundreds of primary particles manufactured by conventional methods, and refers to a positive electrode active material or lithium transition metal active material composed of 1-50 particles, 1-40 particles, 1-30 particles, 1-20 particles, 1-15 particles, 1-10 particles, or 1-5 particles.

[0055] As used herein, the term "single crystal" is used interchangeably with the term "single crystalline" and refers to a positive electrode active material or lithium transition metal oxide containing up to 50 grains, specifically 1-30 grains. Generally, a single crystal particle means a particle in which the entire sample consists of only a single grain or a grain region. In the present invention, the positive electrode active material or the lithium transition metal oxide in the form of a single particle can exhibit properties similar to those of a single crystal particle by containing a small amount of grains.

[0056] "Single particle" refers to the smallest unit of a particle identified when observing the positive active material by a scanning electron microscope, and "grain" or "grain region" refers to a region in which atoms in a sample are continuously and periodically arranged in one direction. Grains can be analyzed using an electron backscatter diffraction (EBSD) analyzer.

[0057] As used herein, the term "average particle size (D 50 )" refers to the particle size at 50% of the volume cumulative distribution. Regarding the average particle size, D 50 The measurement can be performed by dispersing the powder to be tested in a dispersion medium, introducing the powder into a commercially available laser diffraction particle size measuring instrument (e.g., S3500 manufactured by Microtrac, Inc.), measuring the difference in the diffraction pattern according to the particle size when the particles pass through the laser beam to calculate the particle size distribution, and calculating the particle size at 50% of the volume cumulative distribution based on the particle size in the measuring instrument.

[0058] The positive electrode active material of the present invention comprises: a lithium transition metal oxide, which is in the form of a single particle and is divided into a surface portion and a core; a coating portion, which is formed on the surface portion and contains cobalt; and an island portion, which is discontinuously formed on at least one selected from the surface portion and the coating portion, wherein the island portion contains 0.08-2.50 mol % of at least one selected from aluminum (Al) and zirconium (Zr) based on the total molar number of the positive electrode active material.

[0059] The surface portion of the lithium transition metal oxide in the form of a single particle has a layered (R-3m) structure and has a high NiO content before the cobalt-containing coating portion is formed on the surface portion, and the formation of NiO is induced by the high sintering temperature required to prepare the lithium transition metal oxide in the form of a single particle. NiO contained in the surface portion of the lithium transition metal oxide in the form of a single particle may cause an increase in resistance and a decrease in energy density and output.

[0060] The positive electrode active material of the present invention comprises a cobalt-containing coating formed by mixing a lithium transition metal oxide in the form of a single particle with a cobalt source (raw material) and then heat-treating the mixture, and the coating may be a layer formed during the heat treatment process as cobalt diffuses from the surface of the lithium transition metal oxide in the form of a single particle toward the center. During the formation of the coating, the NiO layer of the surface portion is transformed into a layered structure of nickel cobalt manganese (NCM) oxide, thereby reducing and eliminating the causes of increased resistance, reduced energy density, reduced output, etc., whereby the positive electrode active material of the present invention can exhibit excellent electrochemical performance.

[0061] The island portion is discontinuously formed on any one or more selected from the surface portion and the coating portion, and specifically, may be dispersed and distributed on the surface of at least one selected from the surface portion and the coating portion. That is, the island portion may be formed in the form of an island on the surface of at least one of the cobalt coating layer and the outer surface of the surface portion. The expression "dispersed and distributed" may mean that it is not formed as a whole, but is partially formed and is dispersedly formed.

[0062] Depending on the distribution position of the island portion, the island portion may be mixed with the cobalt of the coating portion to form the island portion, or may be separated from the cobalt to form the island portion. The island portion may contain aluminum as an aluminum oxide such as Al2O3; Li such as LiAlO2, Li5AlO4 or LiAl5O8; h Al i O j Lithium aluminum oxides in the form of; cobalt aluminum oxides such as Co2AlO4; or cobalt aluminum oxides such as LiAlCoO3 or Li x Al y Co 1-y Li O2 (0.9≤x≤1.1, 0.01≤y≤0.1) k Al l Co (1-m) O n The island portion may contain zirconium in the form of zirconium oxide, lithium zirconium oxide, cobalt zirconium oxide or lithium cobalt zirconium oxide.

[0063] The surface portion refers to the outer surface of the lithium transition metal oxide in the form of a single particle, and refers to a region having a predetermined thickness from the outermost surface of the lithium transition metal oxide in the form of a single particle toward the center, specifically refers to a region from the outermost surface of the lithium transition metal oxide in the form of a single particle in the direction toward the center to a depth of 1 nm to 50 nm, specifically 5 nm to 30 nm.

[0064] In addition, the core refers to the interior of the lithium transition metal oxide in the form of a single particle excluding the surface portion.

[0065] Based on the overall surface portion and the coating portion, the Co / Ni value (mol / mol) of cobalt and nickel may satisfy 0.10 to 0.80, specifically 0.15 to 0.80, 0.20 to 0.80, 0.10 to 0.75, 0.15 to 0.75, and more specifically 0.20 to 0.75. When the Co / Ni value is less than the above range, cobalt excessively diffuses into the lithium transition metal oxide particles in the form of single particles, so that the cobalt concentration of the surface layer is reduced, resulting in difficulty in exhibiting the effect of the cobalt coating, and in the process of excessive diffusion of cobalt into the particles, a NiO degradation layer may be formed again on the particle surface. In addition, when the Co / Ni value is greater than the above range, the coated cobalt may be used as a separate oxide in the form of Co3O4 or lithium cobalt oxide (Li x Co y O z ) in the form of a cobalt oxide on the particle surface, in which case the NiO degraded layer of the lithium transition metal oxide in the form of a single particle may not be sufficiently transformed into a layered structure of nickel cobalt manganese (NCM) oxide, and an unnecessary amount of cobalt coating formed on the surface of the lithium transition metal oxide may act as a resistor or may cause a capacity decrease.

[0066] The coating portion may be formed on the outer surface of the surface portion, i.e., the outermost surface of the lithium transition metal oxide in the form of a single particle, may be formed on a portion or all of the outer surface of the surface portion, and may be formed in a region of 10% to 100% (area %) based on the total outer surface area of ​​the surface portion. Specifically, the cobalt coating may be formed on a portion of the outer surface of the surface portion, and may be formed in a region of 30% to 90% based on the total outer surface area of ​​the surface portion.

[0067] The coating part may be formed in the form of islands on the outer surface of the surface part. The island form refers to a shape formed discontinuously on the outer surface of the surface part, that is, the coating part may be partially dispersed and distributed on the outermost surface of the lithium transition metal oxide in the form of a single particle.

[0068] The coating portion may include a composition of LiCoO 2 , and specifically, the coating portion may be included as LiCoO 2 in the form of islands on the outer surface of the surface portion.

[0069] The surface portion may have a layered (R-3m) structure, the average oxidation number of the nickel (Ni) contained in the surface portion may be +2.36 to +3.00, and the average oxidation number of the nickel contained in the surface portion may be +2.36 to +2.95, +2.36 to +2.91, +2.37 to +2.95, more specifically +2.37 to +2.91. The average oxidation number of the nickel contained in the surface portion may vary with the coating amount of cobalt forming the coating portion, and when the above range is met, an appropriate amount of coating portion is formed on the surface, so that the NiO degraded layer of the lithium transition metal oxide is fully transformed into a layered structure of nickel cobalt manganese (NCM) oxide, thereby preventing the problem of cation mixing and structural instability caused by the collapse of the layered structure of the NiO degraded layer. Therefore, the surface portion may include a layered structure of nickel cobalt manganese oxide transformed from the NiO layer.

[0070] In addition, in the positive electrode active material according to one example of the present invention, the average oxidation number of nickel (Ni) from the outermost surface of the lithium transition metal oxide in the form of a single particle in the direction toward the center to a depth of 10 nm can be +2.50 to +3.00, specifically +2.50 to +2.95, +2.50 to +2.90, +2.50 to +2.88, +2.52 to +2.95, +2.52 to +2.90 or +2.52 to +2.88, more specifically +2.54 to +2.86. If the average oxidation number of nickel satisfies the average oxidation number range up to 10 nm, nickel can show an oxidation number gradient in the surface portion, and an appropriate reduction effect can be obtained for the NiO degraded layer of the lithium transition metal oxide in the form of a single particle.

[0071] Based on the total molar number of the positive electrode active material, the island portion contains 0.08-2.50 mol% of at least one selected from aluminum (Al) and zirconium (Zr), specifically 0.09-2.50 mol%, 0.09-2.30 mol%, 0.09-2.00 mol%, 0.09-1.80 mol%, 0.09-1.70 mol%, 0.09-1.60 mol%, 0.09-1.50 mol%, 0.10-2.30 mol%, 0.10-2.00 mol%, 0.10-1.80 mol%, 0.10-1.70 mol%, 0.10-1.60 mol%, 0.10-1.50 mol, 0.13-2.30 mol%, 0. .13-2.00 mol%, 0.13-1.80 mol%, 0.13-1.70 mol%, 0.13-1.60 mol%, 0.13-1.50 mol%, 0.14-2.30 mol%, 0.14-2.00 mol%, 0.14-1.80 mol%, 0.14-1.70 mol%, 0.14-1.60 mol%, 0.14-1.50 mol%, 0.15-2.30 mol%, 0.15-2.00 mol%, 0.15-1.80 mol%, 0.15-1.70 mol%, 0.15-1.60 mol% or 0.15-1.50 mol%, more specifically 0.18-1.00 mol%.

[0072] More specifically, when the island portion contains aluminum, based on the total molar number of the positive electrode active material, the island portion may contain 0.13-2.50 mol % of aluminum, specifically 0.13-2.30 mol %, 0.13-2.00 mol %, 0.13-1.80 mol %, 0.13-1.70 mol %, 0.13-1.60 mol %, 0.13-1.50 mol %, 0.14-2.30 mol %, 0.14-2.00 mol %, 0.14-2.00 mol %, 0.14-2.00 mol %, 0.14-2.00 mol %, 0.14-2.3 ...3-2.30 mol %, 0.13-2.00 mol %, 0.13-2.30 mol %, 0.13-2.00 mol %, 0.13-2.00 mol %, 0.13-2.30 mol %, 0.13-2.00 mol %, 0.13-2. mol%, 0.14-1.80 mol%, 0.14-1.70 mol%, 0.14-1.60 mol%, 0.14-1.50 mol%, 0.15-2.30 mol%, 0.15-2.00 mol%, 0.15-1.80 mol%, 0.15-1.70 mol%, 0.15-1.60 mol% or 0.15-1.50 mol%, more specifically 0.18-1.00 mol%. In addition, when the island portion contains zirconium, the island portion may contain 0.08-2.50 mol % of zirconium, specifically 0.09-2.50 mol %, 0.09-2.30 mol %, 0.09-2.00 mol %, 0.09-1.80 mol %, 0.09-1.70 mol %, 0.09-1.60 mol %, 0.09-1.50 mol %, 0.10-2.30 mol %, 0.10-2.00 mol %, 0.10-1.80 mol %, 0.10-1.70 mol %, 0.09-1.60 mol %, 0.09-1.50 mol %, 0.10-2.30 mol %, 0.10-2.00 mol %, 0.10-1.80 mol %, 0.10-1.70 mol %, 0.14-2.30 mol%, 0.14-2.00 mol%, 0.14-1.80 mol%, 0.14-1.70 mol%, 0.14-1.60 mol%, or 0.14-1.50 mol%. In this case, the total amount of aluminum and zirconium may satisfy the content range of at least one selected from aluminum and zirconium as described above.

[0073] When the total molar number of at least one selected from aluminum and zirconium contained in the island portion satisfies the above range, the positive electrode active material can be inhibited from having a side reaction with the electrolyte, thereby showing an effect of improving cycle characteristics such as increasing capacity retention and reducing resistance increase rate. If the content of aluminum, zirconium or a mixture thereof is insufficient, it is not enough to show the effect of containing an appropriate amount of aluminum, zirconium or aluminum and zirconium as described above, and if the content is too much, it is difficult to show the effect of including the island portion.

[0074] The lithium transition metal oxide in the form of a single particle may be a lithium composite transition metal oxide containing nickel (Ni), cobalt (Co), and manganese (Mn).

[0075] Specifically, the lithium transition metal oxide in the single-particle form can be a lithium composite transition metal oxide represented by Formula 1 below:

[0076] [Formula 1]

[0077] Li a Ni x Co y M 1 z M 2 1-x-y-z O2

[0078] In Formula 1 above,

[0079] M 1 is at least one selected from Mn and Al,

[0080] M 2 is at least one selected from B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, S, Sr, Ta, La, and Hf,

[0081] 1.0 ≤ a ≤ 1.3, 0.6 ≤ x < 1.0, 0 ≤ y ≤ 0.4 and 0 ≤ z ≤ 0.4.

[0082] In addition, specifically, the lithium transition metal oxide can be a lithium composite transition metal oxide represented by Formula 2 below:

[0083] [Formula 2]

[0084] Li a Ni b Co c Mn d M 1 e O2

[0085] In Formula 2 above,

[0086] M 1 is at least one selected from Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S,

[0087] 0.9 ≤ a ≤ 1.1, 0.8 ≤ b < 1, 0 < c < 0.2, 0 < d < 0.2, 0 ≤ e < 0.1 and b + c + d + e = 1.

[0088] In addition, specifically, the lithium transition metal oxide can be a lithium composite transition metal oxide represented by Formula 3 below:

[0089] [Formula 3]

[0090] Li g Ni h Co i Mn j O2

[0091] In the above formula 3, 0.9≤g≤1.1, 0.8≤h<1, 0<i<0.2, 0<j<0.2 and h+i+j=1.

[0092] Considering the specific surface area and the density of the cathode mixture, the average particle size (D 50 ) may be 1-50 μm, specifically, the average particle size (D 50 ) may be 2-20 μm. The positive electrode active material according to one embodiment of the present invention may be composed of an average particle size (D 50 ) is a single particle type positive electrode active material formed by agglomerating particles with an average particle size of 0.1 µm to 10 µm. If the average particle size of the particles meets the above range, the positive electrode active material may have advantages in rolling ratio, electrode gap, etc., and if the average particle size is less than or greater than the above range, the performance in terms of electrode capacity, life characteristics, resistance, etc. may be deteriorated.

[0093] The present invention also provides a method for manufacturing the positive electrode active material.

[0094] The positive electrode active material can be prepared by a method comprising the following steps:

[0095] 1) mixing lithium transition metal oxide particles in the form of single particles, a cobalt source, and at least one selected from an aluminum source and a zirconium source; and

[0096] 2) The mixture in step 1) is heat treated.

[0097] In step 1), the amount of the cobalt source may be 0.1 mol % to 10 mol %, specifically 0.5 mol % to 5 mol %, and more specifically 1 mol % to 3 mol %, based on the positive electrode active material. If the amount of the cobalt source is less than the amount within the above range, a sufficient cobalt coating may not be formed on the outer surface of the surface portion of the lithium transition metal oxide particle, and if the amount of the cobalt source is greater than the amount within the above range, the cobalt coating may be formed more than necessary, or unreacted cobalt compounds may remain on the particle surface, resulting in disadvantages such as increased resistance and reduced capacity.

[0098] At least one selected from an aluminum source and a zirconium source may be mixed with the cobalt coating to be coated together, or may be formed as a separate coating, and may be formed in the form of islands in at least one selected from a surface portion and a coating portion of a lithium transition metal oxide particle in a single crystal form.

[0099] In step 1), based on the total molar number of the positive electrode active material, the amount of at least one selected from the aluminum source and the zirconium source can be 0.13-2.50 mol%, specifically 0.13-2.30 mol%, 0.13-2.00 mol%, 0.13-1.80 mol%, 0.13-1.70 mol%, 0.13-1.60 mol%, 0.13-1.50 mol%, 0.14-2.30 mol%, 0.14-2 .00 mol%, 0.14-1.80 mol%, 0.14-1.70 mol%, 0.14-1.60 mol%, 0.14-1.50 mol%, 0.15-2.30 mol%, 0.15-2.00 mol%, 0.15-1.80 mol%, 0.15-1.70 mol%, 0.15-1.60 mol% or 0.15-1.50 mol%, more specifically 0.18-1.00 mol%.

[0100] When the amount of at least one selected from the aluminum source and the zirconium source is within the above range, an island portion can be appropriately formed, thereby suppressing the side reaction of the manufactured positive electrode active material with the electrolyte, thereby improving the cycle characteristics such as increasing the capacity retention rate and reducing the resistance increase rate.

[0101] When the amount of at least one selected from the aluminum source and the zirconium source is less than the above range, the aluminum-containing island portion may not be properly formed on the outer surface of the surface portion of the lithium transition metal oxide particle, and when the amount of the aluminum source is greater than the above range, the effect of reducing the degraded NiO layer by the cobalt coating may be deteriorated, and the excessively generated island portion serves as a resistance layer, whereby the performance may be reduced.

[0102] In addition, in step 1), a process of further mixing an additional metal source other than cobalt and aluminum may be performed. The additional metal source may be used together with the cobalt source and the aluminum source to be coated on the surface portion of the lithium transition metal oxide in the form of a single particle through a subsequent step. The coating formed by the additional metal source may be contained in a coating portion formed by the cobalt source, in an island portion formed by at least one selected from an aluminum source and a zirconium source, or in both, or may be formed as a separate metal coating.

[0103] The mixing of step 1) can be dry mixing, for example, mixing a powdered cobalt source material with a lithium transition metal oxide in the form of a single particle in the absence of a solvent. This dry mixing can be a simple mixing process, and can show the advantages of cost reduction and quality stabilization by simplifying the process. In a method for manufacturing a positive electrode active material according to one embodiment of the present invention, lithium transition metal oxide particles in the form of a single particle are dry mixed with a cobalt (Co) source, an aluminum source, a zirconium source, etc., and then heat treated, so that the coating portion can be formed in the form of an island.

[0104] The heat treatment of step 2) can be performed at 500° C. to 800° C., specifically 600° C. to 800° C., and more specifically 650° C. to 750° C. If the heat treatment temperature satisfies the above range, the cobalt coating mixed on the surface of the lithium transition metal oxide in the form of a single particle during the heating process of the heat treatment, specifically the cobalt formed on the surface of the lithium transition metal oxide in the form of an island and existing in the LiCoO2 phase, penetrates into the lithium transition metal oxide in the form of a single particle to an appropriate depth, thereby appropriately changing the NiO layer as a degenerate layer into a layered structure of nickel cobalt manganese (NCM) oxide, and accordingly, the surface portion of the lithium transition metal oxide in the form of a single particle has a layered (R-3m) structure, and the surface portion includes an oxidation number gradient layer in which the oxidation number of nickel increases in the direction toward the outermost surface, thereby showing excellent effects in battery performance such as charge and discharge capacity, initial efficiency, and initial resistance. If the heat treatment temperature in step 2) is low, the thickness of the coating portion increases and the coating portion is excessively formed, making it difficult to exhibit the advantages of forming the coating portion as described above, and if the heat treatment temperature in step 2) is high, cobalt is deeply doped into the lithium transition metal oxide in the form of a single particle, whereby the coating portion may not be properly formed on the surface portion.

[0105] The heat treatment in step 2) can be performed for 2 to 12 hours, specifically 2 to 9 hours, and more specifically 2 to 6 hours. If the heat treatment is performed within the above time range, excellent productivity can be exhibited and uniform sintering can be achieved.

[0106] The cobalt source can be an oxide, hydroxide, oxyhydroxide, carbonate, sulfate, halide, sulfide, acetate, nitrate, carboxylate, a combination thereof, etc. containing cobalt, for example, it can include Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, Co(SO4)2·7H2O, etc., and any one of them or a mixture of two or more thereof can be used, specifically, Co(OH)2 can be used.

[0107] The aluminum source can be an oxide, hydroxide, hydroxyhydroxide, carbonate, sulfate, halide, sulfide, acetate, nitrate, carboxylate, a combination thereof, etc. containing aluminum, for example, it can include Al2O3, Al(OH)3, Al2(SO4)3, AlCl3, Al isopropoxide, Al(NO3)3, AlF3, etc., but is not limited thereto.

[0108] In addition, the zirconium source may be an oxide, hydroxide, hydroxyhydroxide, carbonate, sulfate, halide, sulfide, acetate, nitrate, carboxylate, a combination thereof, etc. containing zirconium, but is not limited thereto.

[0109] The additional metal source may be, for example, an oxide, hydroxide, hydroxyhydroxide, carbonate, sulfate, halide, sulfide, acetate, nitrate, carboxylate or a combination thereof containing at least one element selected from the following: Ti, W, B, F, P, Mg, Fe, Cr, V, Cu, Ca, Zn, Nb, Mo, Sr, Sb, Bi, Si, Cr, Hf, Ta, La, Ba, Ce, Sn, Y and S, and may specifically include ZnO, TiO2, WO3, H2BO3, HBO2, H3BO3, H2B4O7, B2O3, C6H5B(OH)2, (C6H5O)3B, (CH3(CH2)3O)3B, C3H9B3O6, (C3H7O3)B, Li3WO4, (NH4) 10 W 12 O 41 5H2O, NH4H2PO4, etc., but not limited thereto.

[0110] The amount of the additional metal source can be such that the total amount of the additional metal and aluminum is 100 ppm to 50,000 ppm, specifically 200 ppm to 10,000 ppm based on the total molar number of the metal in the positive electrode active material. If the content of the additional metal together with aluminum is within the above range, the effect of effectively suppressing the side reaction with the electrolyte can be expected, and the electrochemical properties can be further improved.

[0111] In one example of the present invention, lithium transition metal oxide particles in the form of single particles may be prepared by mixing a transition metal oxide precursor and a lithium raw material to perform primary sintering, decomposing a pre-sintered product prepared by the primary sintering, and then performing secondary sintering.

[0112] According to another embodiment of the present invention, a positive electrode including the positive electrode active material is provided.

[0113] Specifically, the positive electrode includes a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including the above-mentioned positive electrode active material.

[0114] The positive electrode current collector is not particularly limited as long as it has conductivity without causing adverse chemical changes in the battery, and for example: stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, the thickness of the positive electrode current collector can generally be 3 μm-500 μm, and fine concavoconvexity can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam body, and a non-woven fabric body.

[0115] The positive electrode active material layer may further include a conductive material and a binder in addition to the above-mentioned positive electrode active material.

[0116] In this case, the conductive material is used to provide conductivity to the electrode, and any conductive material can be used without particular limitation as long as it has electronic conductivity and does not cause adverse chemical changes in the battery to be constructed. Specific examples of conductive materials can be: graphite such as natural graphite or artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; powder or fiber of metals such as copper, nickel, aluminum and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof can be used. The content of the conductive material can generally be 1% to 30% by weight based on the total weight of the positive electrode active material layer.

[0117] Binder is used to improve the bonding between positive active material particles and the adhesion between positive active material and current collector. Specific examples of binders can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-to-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof can be used. Based on the gross weight of the positive active material layer, the content of the binder can be 1% to 30% by weight.

[0118] In addition to using the above-mentioned positive electrode active material, the positive electrode can be prepared according to a conventional method for preparing a positive electrode. Specifically, a positive electrode active material-forming composition prepared by mixing or dispersing the above-mentioned positive electrode active material and an optional binder and a conductive material in a solvent is coated on a positive electrode collector, and then the positive electrode can be prepared by drying and rolling the coated positive electrode collector. In this case, the types and contents of the positive electrode active material, the binder and the conductive material are the same as those described above.

[0119] The solvent may be a commonly used solvent in the art. The solvent may include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, and any one thereof or a mixture of two or more thereof may be used. If the coating thickness and manufacturing yield of the slurry are taken into account, the solvent may dissolve or disperse the positive electrode active material, the conductive material and the binder, and may have a viscosity that can provide excellent thickness uniformity during subsequent coating for preparing the positive electrode, then the amount of the solvent used may be sufficient.

[0120] Furthermore, as another method, the positive electrode may be prepared by casting the positive electrode active material layer-forming composition on a separate support and then laminating the film separated from the support on the positive electrode current collector.

[0121] According to another embodiment of the present invention, an electrochemical device including a positive electrode is provided. The electrochemical device may be a battery or a capacitor, and may be, for example, a lithium secondary battery.

[0122] The lithium secondary battery specifically comprises a positive electrode, a negative electrode arranged to face the positive electrode, a separator arranged between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is as described above. In addition, the lithium secondary battery may further selectively comprise a battery container for accommodating an electrode assembly of the positive electrode, the negative electrode and the separator, and a sealing member for sealing the battery container.

[0123] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0124] The negative electrode current collector is not particularly limited as long as it has high conductivity without causing adverse chemical changes in the battery, and for example: copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloys can be used. In addition, the thickness of the negative electrode current collector can generally be 3 μm to 500 μm, and similar to the positive electrode current collector, fine concavoconvexities can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0125] The negative electrode active material layer optionally contains a binder and a conductive material in addition to the negative electrode active material.

[0126] A compound capable of reversibly inserting and extracting lithium can be used as a negative electrode active material. Specific examples of negative electrode active materials may be the following substances: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; (semi)metallic materials capable of forming alloys with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; (semi)metallic oxides such as SiO2 that may be doped or undoped with lithium; x(0 < x < 2), SnO2, vanadium oxides, and lithium vanadium oxides; or composite materials containing (semi) metallic materials and carbonaceous materials such as Si-C composite materials or Sn-C composite materials, and any one of them or a mixture of two or more of them can be used. Additionally, a thin film of metallic lithium can be used as the negative electrode active material. Furthermore, both low-crystalline carbon and high-crystalline carbon can be used as the carbon material. Typical examples of low-crystalline carbon can be soft carbon and hard carbon, and typical examples of high-crystalline carbon can be natural graphite or artificial graphite, condensated graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microbeads, mesophase pitch, and high-temperature sintered carbon such as coke derived from petroleum or coal tar pitch, which are irregular, plate-like, scaly, spherical, or fibrous.

[0127] In addition, the binder and the conductive material can be the same as those described in the positive electrode above.

[0128] The negative electrode active material layer can be prepared, for example, by coating a negative electrode forming composition prepared by dispersing the negative electrode active material and optionally a binder and a conductive material in a solvent on a negative electrode current collector and drying it, or it can be prepared by casting the negative electrode forming composition on a separate carrier and then laminating the film obtained by peeling from the carrier on the negative electrode current collector.

[0129] On the other hand, in a lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for the movement of lithium ions. Any separator can be used as this separator without particular limitation as long as it is commonly used in lithium secondary batteries. In particular, a separator having a high moisture retention capacity for the electrolyte and a low resistance to the movement of electrolyte ions can be used. Specifically, a porous polymer film, for example, a porous polymer film prepared from polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, can be used; or a laminated structure having two or more layers thereof. In addition, a conventional porous non-woven fabric, for example, a non-woven fabric formed from high melting point glass fibers or polyethylene terephthalate fibers, can be used. Furthermore, a coated separator containing a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multi-layer structure can be optionally used.

[0130] In addition, the electrolyte used in the present invention can include, but is not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, or molten-type inorganic electrolytes that can be used to manufacture lithium secondary batteries.

[0131] Specifically, the electrolyte can contain an organic solvent and a lithium salt.

[0132] Any organic solvent can be used as the organic solvent without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, the following substances can be used as organic solvents: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; or carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2-C20 hydrocarbon group and may contain a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. Among these solvents, carbonate solvents can be used, for example, a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ion conductivity and high dielectric constant that can improve the charge / discharge performance of the battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) can be used. In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte can be excellent.

[0133] Lithium salts can be used without particular limitation, as long as it is a compound that can provide lithium ions used in lithium secondary batteries. Specifically, the following substances can be used as the lithium salts: LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. Lithium salts are preferably used in a concentration range of 0.1 M to 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte can have suitable conductivity and viscosity, thereby showing excellent performance, and lithium ions can be effectively moved.

[0134] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and improve the discharge capacity of the battery, in addition to the electrolyte components, the electrolyte may further contain at least one additive, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride. In this case, the content of the additive may be 0.1 wt % to 5 wt % based on the total weight of the electrolyte.

[0135] As described above, since the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and capacity retention rate, the lithium secondary battery is suitable for: portable devices such as mobile phones, notebook computers and digital cameras; and electric vehicles such as hybrid electric vehicles (HEV).

[0136] Therefore, according to another embodiment of the present invention, a battery module including the lithium secondary battery as a unit battery and a battery pack including the battery module are provided.

[0137] The battery module or battery pack can be used as a power source for at least one of the following medium to large devices: power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); or power storage systems.

[0138] The shape of the lithium secondary battery of the present invention is not particularly limited, but a cylindrical type using a can, a prismatic type, a pouch type, or a coin type can be used.

[0139] The lithium secondary battery according to the present invention can be used not only in a battery cell used as a power source for small devices but also as a unit battery in a medium or large battery module including a plurality of battery cells.

[0140] Example

[0141] Hereinafter, examples of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be embodied in many different forms and should not be construed as being limited to the examples set forth herein.

[0142] Preparation Example 1

[0143] The positive electrode active material precursor (composition: Ni 0.95 Co 0.03 Mn 0.02 (OH)2, average particle size (D 50 ) is 3.5 µm) and LiOH as a lithium raw material are mixed in a molar ratio of 1:1.05, the mixture is once sintered at 850°C in an oxygen atmosphere for 9 hours to prepare a pre-sintered product, the pre-sintered product is decomposed, and then secondarily sintered at 750°C in an oxygen atmosphere for 9 hours to prepare a lithium transition metal oxide in the form of a single particle.

[0144] Example 1

[0145] The single particle lithium transition metal oxide prepared in Preparation Example 1, the powdered cobalt source Co(OH)2 (Huayou Cobalt Co., Ltd.) and the powdered aluminum source Al(OH)3 were mixed in amounts of 97.82 mol%, 2 mol% and 0.18 mol%, respectively.

[0146] The mixture was heat-treated at 700° C. for 5 hours to obtain a cake-shaped positive electrode active material, which was pulverized to prepare a single particle type positive electrode active material in the form of powder.

[0147] Example 2

[0148] A single particle type positive electrode active material in powder form was prepared in the same manner as in Example 1, except that the aluminum source Al(OH) 3 was used in an amount of 0.5 mol % and the amount of the lithium transition metal oxide was adjusted accordingly.

[0149] Example 3

[0150] A single particle type positive active material in powder form was prepared in the same manner as in Example 1, except that the aluminum source Al(OH) 3 was used in an amount of 1 mol % and the amount of the lithium transition metal oxide was adjusted accordingly.

[0151] Example 4

[0152] The lithium transition metal oxide in the form of single particles prepared in Preparation Example 1, the cobalt source Co(OH)2 (Huayou Cobalt Co., Ltd.) in powder form, and the zirconium source ZrO2 in powder form were mixed in amounts of 97.92 mol%, 2 mol%, and 0.08 mol%, respectively.

[0153] The mixture was heat-treated at 700° C. for 5 hours to obtain a cake-shaped positive electrode active material, which was pulverized to prepare a single particle type positive electrode active material in the form of powder.

[0154] Example 5

[0155] A single particle type positive electrode active material in powder form was prepared in the same manner as in Example 4, except that the zirconium source ZrO 2 was used in an amount of 0.5 mol % and the amount of the lithium transition metal oxide was adjusted accordingly.

[0156] Example 6

[0157] A single particle type positive electrode active material in powder form was prepared in the same manner as in Example 4, except that the zirconium source ZrO 2 was used in an amount of 1 mol % and the amount of the lithium transition metal oxide was adjusted accordingly.

[0158] Comparative Example 1

[0159] The lithium transition metal oxide in the form of a single particle prepared in the above Preparation Example 1 was used as a positive electrode active material in the form of a single particle.

[0160] Comparative Example 2

[0161] The lithium transition metal oxide in the form of single particles prepared in Preparation Example 1 and a cobalt source Co(OH)2 (Huayou Cobalt Co., Ltd.) in the form of powder were mixed in amounts of 98 mol % and 2 mol %, respectively.

[0162] The mixture was heat-treated at 700° C. for 5 hours to obtain a cake-shaped positive electrode active material, which was pulverized to prepare a single particle type positive electrode active material in the form of powder.

[0163] Comparative Example 3

[0164] A single particle type positive active material in powder form was prepared in the same manner as in Example 1, except that the aluminum source Al(OH) 3 was used in an amount of 0.1 mol % and the amount of the lithium transition metal oxide was adjusted accordingly.

[0165] Comparative Example 4

[0166] A single particle type positive active material in powder form was prepared in the same manner as in Example 1, except that the aluminum source Al(OH) 3 was used in an amount of 3 mol % and the amount of the lithium transition metal oxide was adjusted accordingly.

[0167] Comparative Example 5

[0168] The lithium transition metal oxide in the form of single particles prepared in Preparation Example 1, the cobalt source Co(OH)2 (Huayou Cobalt Co., Ltd.) in powder form, and the aluminum source Al(OH)3 in powder form were mixed in amounts of 99.48 mol%, 0.02 mol%, and 0.5 mol%, respectively.

[0169] The mixture was heat-treated at 700° C. for 5 hours to obtain a cake-shaped positive electrode active material, which was pulverized to prepare a single particle type positive electrode active material in the form of powder.

[0170] Comparative Example 6

[0171] The single particle lithium transition metal oxide prepared in Preparation Example 1, the powdered cobalt source Co(OH)2 (Huayou Cobalt Co., Ltd.) and the powdered zirconium source ZrO2 were mixed in amounts of 99.48 mol%, 0.02 mol% and 0.5 mol%, respectively.

[0172] The mixture was heat-treated at 700° C. for 5 hours to obtain a cake-shaped positive electrode active material, which was pulverized to prepare a single particle type positive electrode active material in the form of powder.

[0173] Experimental Example 1

[0174] 1) EELS measurement and confirmation of Ni oxidation number

[0175] The positive electrode active material powder was made into a thin film sample with a thickness of 100 nm to 200 nm using a Helios G4 UX FIB device manufactured by FEI Co., Ltd., and the Ni L3 energy loss spectrum of the sample was measured using a Titan G2 80-200ChemiSTEM device and a Gatan Continuum S EELS system manufactured by FEI Co., Ltd. 2+ and Ni 3+ With reference to the spectrum, the average Ni oxidation number of the surface portion to a depth of 10 nm from the outermost portion of the positive electrode active material in a direction toward the center was measured by nonlinear least square fitting.

[0176] 2) Measurement of Co / Ni in the surface

[0177] The Co / Ni content ratio of the surface of the positive electrode active material powder to a depth of 10 nm was measured by electron spectroscopy chemical analysis (ESCA) for chemical analysis using a K-alpha XPS apparatus manufactured by Thermo Fisher Inc., and the results are shown in Table 1.

[0178]

[0179] Referring to Table 1, Examples 1 to 3 satisfy the following conditions: the number of moles of aluminum contained in the island portion is 0.13-2.50 mol% based on the total number of moles of the positive electrode active material, and the nickel contained in the surface portion shows an oxidation number in the range of +2.4 to +3. Examples 4 to 6 satisfy the following conditions: the number of moles of zirconium contained in the island portion is 0.13-2.50 mol% based on the total number of moles of the positive electrode active material, and the nickel contained in the surface portion shows an oxidation number in the range of +2.4 to +3. It was thus confirmed that, compared with the composition of the lithium transition metal oxide in the form of a single particle, the positive electrode active materials of Examples 1 to 6 cause an increase in the ratio of cobalt on the surface portion due to the influence of the cobalt coating layer formed on the outer surface of the surface portion of the lithium transition metal oxide in the form of a single particle, and an increase in the oxidation number of the contained Ni, thereby reducing the NiO-type degenerate layer in which the oxidation state of nickel present on the surface portion of the positive electrode active material is +2.

[0180] On the other hand, it was confirmed that Comparative Examples 1 to 3 did not satisfy the following condition: the molar number of aluminum contained in the island portion was 0.13-2.50 mol% based on the total molar number of the positive electrode active material. In addition, Comparative Examples 1 and 4 to 6 showed that the Ni oxidation number was less than +2.4, thereby confirming that a large amount of NiO-type degraded layer containing nickel with an oxidation state of +2 was present on the surface portion.

[0181] on the other hand, Figure 1 and Figure 2 An image of a cross section of the single-particle type positive electrode active material of Example 1 is shown. Figure 1 The left side is a TEM image of the particle (index: HAADF), the middle is a TEM EDS image that can confirm the Al coating (index: AlKa), and the right side is a TEM EDS image that can confirm the Co coating (index: Co Ka). Figure 1 It could be confirmed that a cobalt coating layer was formed on the surface of the particles, and an aluminum coating layer was formed on the cobalt coating layer or the surface of the particles. Figure 2 A TEM EDS image (index: Al-Ka) obtained from another position that can confirm an Al coating and a TEM EDS image (index: Co-Ka) that can confirm a Co coating are shown. Figure 2 It was confirmed that the cobalt coating layer and the aluminum coating layer were formed on the outer surface of the surface portion of the lithium transition metal oxide in the form of a single particle and in the form of islands.

[0182] Experimental Example 2

[0183] Cathode Manufacturing

[0184] The positive electrode active material prepared in Example 1, carbon black (Denka Black, Denka Co., Ltd.) as a conductive material, and PVdF (KF1300, Kureha Co., Ltd.) as a binder were added to a solvent (N-methylpyrrolidone (NMP), Daejung Chemicals, Co., Ltd.) at a weight ratio of 95:3:2 (positive electrode active material: conductive material: binder) to prepare a composition for forming a positive electrode active material layer.

[0185] The prepared positive electrode active material layer-forming composition was coated on one surface of an aluminum foil current collector having a thickness of 20 μm and dried at 135° C. for 3 hours to form a positive electrode active material layer. Subsequently, the positive electrode active material layer was rolled by a rolling method, and a positive electrode was manufactured after rolling, wherein the porosity of the positive electrode active material layer was 20%.

[0186] Positive electrodes were prepared in the same manner as the above method by using the positive electrode active materials of Examples 2 to 6 and Comparative Examples 1 to 6, respectively, instead of the positive electrode active material prepared in Example 1.

[0187] Using metallic lithium as a negative electrode and the positive electrode, a coin half-cell was manufactured.

[0188] Evaluation of electrochemical performance

[0189] Using the half-cell fabricated as described above, the electrochemical performance was evaluated as follows.

[0190] Each of the manufactured coin half cells was charged at a constant current (CC) of 0.2C at 25°C until it reached 4.25 V, and then charged at a constant voltage (CV) of 4.25 V, and the charge capacity was measured by performing charging once until the charge current reached 0.05 mAh. Thereafter, the coin half cell was left to stand for 20 minutes, and then discharged at a constant current of 0.2C until it reached 2.5 V to measure the discharge capacity of the first cycle. The charge and discharge efficiency of the first cycle was evaluated.

[0191] The coin half cell was fully charged in the same manner and a discharge current of 0.2 C was applied thereto for 10 seconds to measure the initial resistance (DCIR) by dividing the voltage difference between just before and 10 seconds after the current application by the current.

[0192] The battery that completed one cycle was transferred to a chamber at 45°C, and charging and discharging were repeated at 0.33 C until the 50th cycle, and the discharge capacity of the 50th cycle was measured to calculate the ratio of the discharge capacity of the 50th cycle to the discharge capacity of the first cycle, thereby evaluating the capacity retention rate. In addition, while the battery was discharged at a constant current (CC) of 0.2 C until it reached 2.5 V at the 50th cycle, the voltage change from the fully charged state until the discharge for 10 seconds was divided by the current to measure the discharge resistance at the 50th cycle (50th DCR), and the ratio of the discharge resistance of the 50th cycle to the initial resistance (1st DCR) was calculated to obtain the resistance increase rate (%). The results are shown in Table 2.

[0193]

[0194] Referring to Table 2, Examples 1 to 6 satisfying the condition that the molar number of aluminum or the molar number of zirconium contained in the island portion is 0.13-2.50 mol % based on the total molar number of metal in the lithium transition metal oxide simultaneously satisfy high discharge capacity, excellent capacity retention rate and low resistance increase rate, but Comparative Examples 1 to 4 not satisfying the above conditions have worse capacity retention rate and resistance increase rate than Examples 1 to 6, and also exhibit low discharge capacity.

[0195] Comparative Example 1 uses the lithium transition metal oxide in the form of a single particle prepared in Preparation Example 1 as a positive electrode active material as it is, and does not include a cobalt coating on the outer surface of the surface portion. In Comparative Example 1, the discharge capacity, capacity retention rate, and resistance increase rate are all poor, and it is believed that this is due to the presence of NiO contained in the surface portion of the lithium transition metal oxide in the form of a single particle, as can be seen from the fact that the positive electrode active material of Comparative Example 1 shows a low oxidation number of +2.21 and a low Co / Ni ratio of 0.06. In addition, in Comparative Examples 5 and 6, it can be seen that the cobalt-containing coating portion is not properly formed on the outer surface of the surface portion of the lithium transition metal oxide in the form of a single particle as in Example 1, thereby being poor in terms of discharge capacity, capacity retention rate, and resistance increase rate. Comparative Examples 5 and 6 are also believed to exhibit worse performance than Examples 1 to 6 due to the presence of NiO contained in the surface portion of the lithium transition metal oxide in the form of a single particle.

[0196] In addition, the discharge capacity, capacity retention rate and resistance increase rate of Comparative Example 4 were also poor, and the total molar number of aluminum contained in Comparative Example 4 was 3% based on the total molar number of the single particle type positive electrode active material, and the aluminum content was too high. Referring to Table 1, in Comparative Example 4 in which the total molar number of aluminum contained was 3 mol%, it was confirmed that the oxidation number of nickel in the surface portion (up to 10 nm) was +2.28 and the Co / Ni ratio in the surface portion was 0.86, and it was confirmed that if the coating amount of aluminum increased, the NiO degenerate layer was not sufficiently converted into a layered structure of nickel cobalt manganese (NCM) oxide, although the coating amount of cobalt was equal to that of Examples 1 to 6, and thus the effect of reducing the NiO layer appropriately could not be obtained, and it was also confirmed by the decrease in charge capacity compared with Comparative Example 1 that the excessive Al composite compound coating acted as an additional resistor.

[0197] On the other hand, Comparative Example 2 is a positive electrode active material including a cobalt coating but not an aluminum-containing island portion, and Comparative Example 3 includes both a cobalt coating and an aluminum-containing island portion, and the aluminum content is 0.1 mol% in total, which is insufficient. Referring to Table 1, the positive electrode active materials of Comparative Examples 2 and 3 show similar levels to Examples 1 to 3 in terms of the oxidation number of nickel and the Co / Ni ratio in the surface portion, thereby confirming that the NiO degradation layer is transformed into a layered structure of nickel cobalt manganese (NCM) oxide. However, it is confirmed that the capacity retention rate of 50 cycles and the resistance increase rate of 50 cycles of the positive electrode active materials of Comparative Examples 2 and 3, in which the outermost surface does not contain an aluminum-containing island portion or the total amount of aluminum contained in the outermost surface of the island portion is insufficient, are worse than those of the positive electrode active materials of Examples 1 to 6, and thus the life characteristics are worse.

[0198] It was thus confirmed that if a coating portion containing cobalt was included on the surface portion and an appropriate amount of aluminum was included in the outermost portion of the island portion, a side reaction with the electrolyte was effectively suppressed, thereby improving life characteristics.

Claims

1. A positive electrode active material, the positive electrode active material comprising: a lithium transition metal oxide, the lithium transition metal oxide being in the form of single particles and divided into a surface portion and a core; a coating portion, the coating portion being formed on the surface portion and containing cobalt; and island portions, the island portions being discontinuously formed on at least one of the surface portion and the coating portion, in, based on the total molar number of the positive electrode active material, the island portions containing 0.08 mol% - 2.50 mol% of at least one selected from aluminum and zirconium.

2. The positive electrode active material according to claim 1, wherein The island portions are dispersed and distributed on the surface of at least one of the surface portion and the coating portion.

3. The positive electrode active material according to claim 1, wherein Based on the total molar number of the positive electrode active material, the island portions contain 0.13 mol% - 2.50 mol% of aluminum.

4. The positive electrode active material according to claim 1, wherein Based on the total molar number of the positive electrode active material, the island portions contain 0.08 mol% - 2.50 mol% of zirconium.

5. The positive electrode active material according to claim 1, wherein Based on the total surface area of the outer surface of the lithium transition metal oxide, the total surface area of the coating portion is 10% to 100%.

6. The positive electrode active material according to claim 1, wherein The surface portion is a region from the outermost surface of the single-particle lithium transition metal oxide in the direction toward the center to a depth of 1 nm to 50 nm.

7. The positive electrode active material according to claim 1, wherein The average oxidation number of nickel contained in the surface portion is +2.36 to +3.

00.

8. The positive electrode active material according to claim 1, wherein Based on the entirety of the surface portion and the coating portion, cobalt and nickel satisfy a Co / Ni value (mol / mol) of 0.1 to 0.

8.

9. The positive electrode active material according to claim 1, wherein The coating portion is located on the outer surface of the surface portion in the form of islands.

10. The positive electrode active material according to claim 1, wherein The coating portion contains the composition of LiCoO2.

11. The positive electrode active material according to claim 1, wherein The island portions contain LiCoAlO2.

12. The positive electrode active material according to claim 1, wherein The lithium transition metal oxide is a lithium composite transition metal oxide containing nickel, cobalt, and manganese.

13. The positive electrode active material according to claim 1, wherein The lithium transition metal oxide is a lithium composite transition metal oxide represented by the following Formula 1: [Formula 1] Li a Ni x Co y M 1 z M 2 1-x-y-z O2 wherein, in Formula 1 above, M 1 is at least one selected from Mn and Al, M 2 is at least one selected from the group consisting of B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, S, Sr, Ta, La and Hf, 1.0 ≤ a ≤ 1.3, 0.6 ≤ x < 1.0, 0 ≤ y ≤ 0.4 and 0 ≤ z ≤ 0.

4.

14. The positive electrode active material according to claim 1, wherein The lithium transition metal oxide is a lithium composite transition metal oxide represented by the following Formula 2: [Formula 2] Li a Ni b Co c Mr d M 1 e O2 wherein, in Formula 2 above, M 1 is at least one selected from the group consisting of Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P and S, 0.9 ≤ a ≤ 1.1, 0.8 ≤ b < 1, 0 < c < 0.2, 0 < d < 0.2, 0 ≤ e < 0.1 and b + c + d + e = 1.

15. A method for manufacturing the positive electrode active material according to claim 1, the method comprising the following steps: 1) Mixing single-particle lithium transition metal oxide particles, a cobalt source, and at least one selected from an aluminum source and a zirconium source; and 2) Heat-treating the mixture in step 1).

16. The method according to claim 15, wherein: In step 1), an additional metal source is further mixed.

17. The method according to claim 15, wherein: The heat treatment in step 2) is carried out at 500°C - 800°C.

Citation Information

Patent Citations

  • System for noise alarming between floors

    KR1020190094529A

  • BICM receiving device for QPSK and low density parity check codeword with 16200 length, 3 / 15 rate, and method using the same

    KR1020220062251A